Y = -2x + b
Plug in the point
7 = -2(-1) + b
7 = 2 + b
b = 5
Final equation y = -2x + 5
Answer:
Step-by-step explanation:
Answer:
(x,y) = (-2, -1)
Step-by-step explanation:
We start off by substituting the value of "x".
5x+7y=-17
x=-![\frac{5}{4} + \frac{3}{4}y](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D%20%2B%20%5Cfrac%7B3%7D%7B4%7Dy)
We then solve 5![5(-\frac{5}{4}+\frac{3}{4}y ) +7y= -17](https://tex.z-dn.net/?f=5%28-%5Cfrac%7B5%7D%7B4%7D%2B%5Cfrac%7B3%7D%7B4%7Dy%20%29%20%2B7y%3D%20-17)
y=-1 *Substitute the value of "y"
x= -![-\frac{5}{4}+\frac{3}{4}x(-1)](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B4%7D%2B%5Cfrac%7B3%7D%7B4%7Dx%28-1%29)
x=-2
This works.
14 hundreds, 10 tens, and 2 ones.
A) sum 3 + 7 =10
b) divide <span> £</span>300 ÷ 10 = <span> £</span>30
c) multiply:
3 x 30 = <span> £</span>90
7 x 30 = <span> £</span>210
Values are: £90 and <span> £210</span>